A rare case of postoperative Fournier’s gangrene after a hemorrhoidectomy - Alla, Mrinalini; Bodden, Chloe; Kiarie, Patrick Kamere; Khan, Noman; Louis, Martine A.; Mandava, Neil (International Surgery Journal, 2024)
Fournier’s gangrene (FG) is a severe and fulminant necrotizing fasciitis of the perineal, genital, and perianal regions. Extensive postoperative infections after anorectal surgeries are rare, and the development of FG after hemorrhoid surgery is extremely rare. We present the case of a 68-year-old diabetic male found to have a severe necrotizing infection of the perianal and perineal region eight days after a hemorrhoidectomy. His hospital course was complicated by septic shock, acute kidney injury, respiratory failure, and multiple strokes. The purpose of this case is to increase awareness of extensive necrotizing infections such as FG, complicating a hemorrhoidectomy, albeit rarely, especially in patients with comorbidities such as diabetes mellitus.